Phytochrome A Mediates Blue-Light Enhancement of Second-Positive Phototropism in Arabidopsis - Sullivan, Stuart; Hart, Jaynee E.; Rasch, Patrick; Walker, Catriona H.; Christie, John M. (Frontiers in Plant Science, 2016)
Hypocotyl phototropism of etiolated Arabidopsis seedlings is primarily mediated by the blue-light receptor kinase phototropin 1 (phot1). Phot1-mediated curvature to continuous unilateral blue light irradiation (0.5 μmol m−2 s−1) is enhanced by overhead pre-treatment with red light (20 μmol m−2 s−1 for 15 min) through the action of phytochrome (phyA). Here, we show that pre-treatment with blue light is equally as effective in eliciting phototropic enhancement and is dependent on phyA. Although blue light pre-treatment was sufficient to activate early phot1 signaling events, phot1 autophosphorylation in vivo was not found to be saturated, as assessed by subsequently measuring phot1 kinase activity in vitro. However, enhancement effects by red and blue light pre-treatment were not observed at higher intensities of phototropic stimulation (10 μmol m−2 s−1). Phototropic enhancement by red and blue light pre-treatments to 0.5 μmol m−2 s−1 unilateral blue light irradiation was also lacking in transgenic Arabidopsis where PHOT1 expression was restricted to the epidermis. Together, these findings indicate that phyA-mediated effects on phot1 signaling are restricted to low intensities of phototropic stimulation and originate from tissues other than the epidermis.